Pengaruh Partisipasi Anggaran, Akuntansi PertanggungJawaban, dan Kepemimpinan terhadap Kinerja Manajerial : Studi Kasus Pada Bank Jakarta - Destiani Andini Syafitri; Wati Rosmawati; Morina Barus (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of budget participation, responsibility accounting, and leadership on managerial performance at Bank Jakarta. Performance is an important factor for continuous improvement and innovation, to measure capabilities, achievements and obstacles in the process of resource utilization, and to achieve appropriate and optimal goals. There are several factors that have the potential to influence managerial performance, namely budget participation, responsibility accounting, and leadership. Where budget participation provides an active role to managers in the company's budget preparation process that can increase managers' understanding of organizational goals, increase motivation, and improve managerial performance. Then, responsibility accounting can measure and control performance based on the responsibilities of each section, thus encouraging managers to act more responsibly towards achieving organizational goals, and can increase work motivation and transparency in performance evaluation. Meanwhile, leadership, where leadership style can shape manager behavior and performance. Participative and supportive leaders can strengthen manager involvement in decision-making and increase loyalty to the organization. This research is a quantitative study. The data collection technique used a questionnaire with a sample of 32 respondents. The collected data was processed for testing using SPSS Version 31. The results of the partial test (t-test) showed that responsibility accounting had a positive and significant effect on managerial performance. Meanwhile, budgetary participation and leadership had no effect on managerial performance. The results of the simultaneous test (f-test) showed that budgetary participation, responsibility accounting, and leadership had an effect on managerial performance.